2022
DOI: 10.3390/coatings12050708
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation and Multi-Objective Parameter Optimization of Inconel718 Coating Laser Cladding

Abstract: Aiming at the difficulty of temperature control in the laser cladding process of high-temperature nickel-based alloys, the influence of cladding parameters on the temperature of the molten pool, and the quality of the cladding layer were explored. Firstly, through the analysis of the finite element method, the Inconel718 single-pass cladding model was established on the surface of 45 steel by using parametric language and life–death element technology, the influence of different laser power and scanning speed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Under the environment of high temperature and high pressure, the colloidal layer is constantly compressed, and the pore structure is constantly reduced until it is compressed into the asphaltene layer, forming a carbon deposit with complex components and dense structure. [26][27][28] In previous studies, carbon deposition was mostly regarded as a process of accumulation on a solid surface. In fact, the entire adhesion process is composed of carbon deposition particles, metal particles, full combustion of lubricating oil, and fuel oil.…”
Section: Adsorption Mechanism Of Carbon Depositionmentioning
confidence: 99%
“…Under the environment of high temperature and high pressure, the colloidal layer is constantly compressed, and the pore structure is constantly reduced until it is compressed into the asphaltene layer, forming a carbon deposit with complex components and dense structure. [26][27][28] In previous studies, carbon deposition was mostly regarded as a process of accumulation on a solid surface. In fact, the entire adhesion process is composed of carbon deposition particles, metal particles, full combustion of lubricating oil, and fuel oil.…”
Section: Adsorption Mechanism Of Carbon Depositionmentioning
confidence: 99%
“…The results showed that the laser power and scanning speed have an influence on the eutectic precipitation, and the eutectic precipitation is positively correlated with the mass gain of the coating. Sirui Yang et al [19] performed multi-objective parameter optimization for laser cladding of IN718 cladding coatings. The validation experiments on single-pass and multi-pass cladding coatings were carried out with the optimal parameters, and it was proved that the process parameters were closely related to the quality of cladding coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Accurately simulating this process is of great significance for obtaining high-quality coatings. Among the various candidate methods, the finite element model is widely utilized as it can offer guidance for selecting laser parameters [15].…”
Section: Introductionmentioning
confidence: 99%